Granulocyte Colony-Stimulating Factor Combined With Transcutaneous Electrical Acupoint Stimulation in Treatment of Unresponsive Thin Endometrium in Frozen Embryo Transfer Cycles - Song, Linjiang; Zhang, Qinxiu; Zhu, Shaomi; Shan, Xudong (Frontiers in Reproductive Health, 2021)
Objective: This trial was designed to assess the treatment effects of granulocyte colony-stimulating factor (G-CSF) and transcutaneous electrical acupoint stimulation (TEAS) on thin endometrium in frozen-thawed embryo transfer (FET) cycles. Methods: Ninety-nine patients with previous cancellations of embryo transfer were included, 56 of whom were prospectively treated with intrauterine perfusion of G-CSF in subsequent FET cycles. The selected patients were randomized into the G-CSF perfusion only group and the G-CSF perfusion combined with TEAS group. The other 43 patients were retrospectively included as controls. Results: Compared to previous cycles, endometrial thickness was statistically significantly increased in the two treatment groups (5.97 ± 0.60, 7.52 ± 0.56, 6.14 ± 0.52, and 7.66 ± 0.44; P = 0.00 and 0.00, respectively). The increases in endometrial thickness suggested that no statistically significant difference was found between the two treatment groups. The G-CSF with TEAS group suggested a higher embryo implantation rate than the G-CSF perfusion only and control groups (33.33 and 29.1% and 33.33 and 17.39%; P = 0.412 and 0.091, respectively). The G-CSF combined with TEAS group demonstrated nominally higher clinical and ongoing pregnancy rates than the G-CSF perfusion-only group and controls, though, the difference was not statistically significant. Conclusion: G-CSF has a potential role in improving endometrium thickness in patients with thin unresponsive endometrium in FET treatment cycles. In addition, when combined with TEAS, G-CSF perfusion treatment also improves the embryo implantation rate; however, randomized controlled trials are highly demanded to provide high-grade evidence regarding clinical pregnancy rate after G-CSF perfusion treatment.